2004
DOI: 10.1186/1477-3155-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a neuronal network direction using stepwise photo-thermal etching of an agarose architecture

Abstract: Control over spatial distribution of individual neurons and the pattern of neural network provides an important tool for studying information processing pathways during neural network formation. Moreover, the knowledge of the direction of synaptic connections between cells in each neural network can provide detailed information on the relationship between the forward and feedback signaling. We have developed a method for topographical control of the direction of synaptic connections within a living neuronal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…BioMEMs involve the use of several different types of probes composed of DNA [470,471], proteins/ peptides [472,473] or cells [474] that are usually arrayed on the chip. Yue et al (Fig.…”
Section: Patterned Sams In Biology and Biomedicinementioning
confidence: 99%
“…BioMEMs involve the use of several different types of probes composed of DNA [470,471], proteins/ peptides [472,473] or cells [474] that are usually arrayed on the chip. Yue et al (Fig.…”
Section: Patterned Sams In Biology and Biomedicinementioning
confidence: 99%
“…An example of an often-used polymer-based fabrication process is replica molding of PDMS [5] using masters created through epoxy polymer photoresist SU-8 photolithography, a micromanufacturing technique developed in the microelectronics industry. A recent trend is to utilize materials more familiar to biologists, such as agarose [6,7] or polystyrene [8] for microfabrication.…”
Section: Reviewmentioning
confidence: 99%
“…Based on observed initial axon growth, microchannels can be opened to connect individual neurons to form simple networks. The panel C is reproduced from [7]. …”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, we developed an agarose microchamber system by using the photothermal etching method [13,14]. This system has been used to control the network patterning of neurons [15-17] and to control the connections of cardiomyocytes [18,19]. Using that system to examine the contribution of the 'community effect' to the stability of the beating in the homogeneous cardiomyocyte networks [20,21], we found that the beating of an in vitro community (network) comprising nine cells is as stable as the beating of the heart, that the rhythms of two isolated cells became synchronized after the cells made physical contact with each other, and that the synchronized rhythm of those two cells was the more stable one rather than the faster one [22].…”
Section: Introductionmentioning
confidence: 99%